Three essays on bureaucracy : post-communist context - Mussagulova, Assel (Nanyang Technological University, 2021)
This thesis comprises three essays united by a common theme of studying bureaucracy in the post-communist context. These essays use secondary data from several major cross-national studies. Post-communist states represent a unique context for exploring the impact of bureaucracy due to their history of transition from the Soviet-style administration to different styles of bureaucratic arrangements depending on the chosen trajectory. In doing so, however, most of these states retained some of the features of the Soviet-style administration (Houston, 2014; Kotchegura, 2008; Liebert, 2014; Meyer-Sahling, 2006, 2011; Neshkova & Kostadinova, 2012; Roots & Karotom, 2002), as a manifestation of path dependency and the resilient nature of institutions. The first essay explores the association between bureaucracy and the quality of public good provision. The overarching framework used in this essay builds on the Weberian model of bureaucracy which is characterised by impartiality, meritocracy, and professionalism. The quality of public good provision is operationalised as the quality of higher education and quality of infrastructure, measured by the World Economic Forum Global Competitiveness Index (2015). The results confirm our hypothesis that bureaucracies that have Weberian features are more likely to provide public goods of higher quality. We further analyse the bureaucratic features in post-communist states and find that the states that are pursuing a policy of rapprochement with the EU are more likely to have bureaucracies modelled after the Weberian ideal type, while those countries that are in close geographical and economic association with Russia have subpar bureaucratic institutions. The second essay investigates the empirical link between bureaucratic closedness and national innovation activity. Bureaucratic closedness refers to the insularity and hierarchy found in bureaucracies, which prioritise loyalty and seniority over performance. This is unlikely to be beneficial for innovation outputs as civil servants in such bureaucracies will be more cautious about expressing initiative and might lack creativity and experience gained in other sectors due to limited career mobility. Results confirm our hypothesis on the negative association between bureaucratic closedness and national innovation activity. We further analyse the data on innovation in post-communist states and find that the evidence for this empirical association in former Soviet countries is mixed. It is more likely that the major contributing factor to innovation in the post-communist context is expenditure on research and development. The third essay aims to understand how bureaucratic features associated with the Soviet-style administration affect intrinsic motivation of public sector employees in post-communist countries. We hypothesise that in the post-communist context public sector employees experience autonomy constraints, associated with the Soviet-style administration, which compromise their intrinsic motivation. Using a multilevel mediation model, we find that the impact of the post-communist context on intrinsic motivation is partially mediated by perceived autonomy fulfilment.